1982
DOI: 10.1111/j.1469-8137.1982.tb03343.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOSYNTHESIS IN DESICCATED SHOOTS OF POLYTRICHUM

Abstract: SUMMARYThe desiccation responses of four species of Polytrichum were examined. The relationship between COj assimilation and shoot water content was similar in Polytrichum commune and Polytrichum piliferum, the species most dissimilar in ecological requirements. There were, however, considerable differences between species in recovery following various desiccation treatments.Continuous desiccation was found to be more damaging than the same total period of desiccation interrupted by periods of wetting. Polytri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…90% of Σ P V for a deciduous shrub with peak season L > 2 m 2 m −2 . High rates of productivity per unit ground area for P. piliferum are consistent with previous studies on excised shoots (Oechel & Collins 1976; Penny & Bayfield 1982). While S. fuscum had lower rates of photosynthesis than P. piliferum , Σ P B was still c .…”
Section: Discussionsupporting
confidence: 91%
“…90% of Σ P V for a deciduous shrub with peak season L > 2 m 2 m −2 . High rates of productivity per unit ground area for P. piliferum are consistent with previous studies on excised shoots (Oechel & Collins 1976; Penny & Bayfield 1982). While S. fuscum had lower rates of photosynthesis than P. piliferum , Σ P B was still c .…”
Section: Discussionsupporting
confidence: 91%
“…During summer then, Polytrichum may have suffered from drier soil, especially in June, which had the lowest soil moisture values of the studied period. It is also possible that warmer and drier conditions may have desiccated its leaves, reducing the plant photosynthetic rate (Penny & Bayfield, 1982). A similar pattern is reported for ridges, which showed a peak in CO 2 uptake in autumn, whereas in summer NEE values were very close to zero.…”
Section: Effect Of Microtopography and Vegetation On Net Ecosystem Exchangesupporting
confidence: 61%
“…Using fern gametophytes it was found that rate of drying was more closely related to recovery than final water content (Watkins et al, 2007). Only a single study has assessed rates of desiccation (as hours at a single RH) under a common RH for bryophytes (Penny and Bayfield, 1982), and although only 3 rates (durations) were employed (6.0, 1.5, and 0.6 h @55% RH), significant recovery differences were found. Our purpose here is to assess DT over a range of rates of desiccation under a given RH considered to represent the presence of DT (50% RH; Koster et al, 2010), potentially allowing the resolution of the fine‐scale effects of rate of desiccation on recovery in an IDT species.…”
Section: Ecological Elements Of Dt In Bryophytesmentioning
confidence: 99%